Creating a sustainable supply chain: the strategic foundation. Issue 6 (19th November 2018) - Orr, Stuart; Jadhav, Akshay
Abstract : Purpose: This paper aims to introduce a supply chain strategy for supply chain sustainability performance and explain why it is different to normal business/operations strategy. Design/methodology/approach: A survey of supply chain managers and detailed case studies of three successful supply chain sustainability organisations identified four components of a supply chain sustainability strategy, the mechanisms behind them and how they interacted. Findings: Sustainability leadership, supply chain member involvement in organisational sustainability initiatives, supply chain member involvement in supply chain sustainability strategy planning and technical competency were identified as the four components of a sustainable supply chain strategy. Sustainability leadership legitimises the objectives and involvement of the staff in supply chain-oriented sustainability initiatives and planning. Technical competency provides the capability and language necessary for the development of a supply chain sustainability strategy. This is different to business/operations strategy, however, parallels to other forms of strategy constructs support its ability to achieve performance improvement. Research limitations/implications: The research is based on data from developed countries; the findings may be different for emerging economies. Potential hypotheses for future research are suggested. Practical implications: The supply chain sustainability strategy will enable organisations to improve the sustainability of their supply chains. Its application is described in the paper. Originality/value: The paper develops a strategy framework different to the approach taken in business/operational strategy. It indicates how the sustainability performance of supply chains external to the organisation is increased through their interconnectedness with the organisation.